2005
DOI: 10.1080/13545700500301163
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Women's Microenterprise Success in Ahmedabad, India: Empowerment and Economics

Abstract: Microenterprise success is often evaluated solely in terms of economic outcomes. These evaluations do not recognize how opportunities for success may differ across groups and contexts, and disregard the importance of power and control as factors in success. This article investigates the determinants of a two-dimensional concept of microenterprise success for women in Ahmedabad, India, by analyzing data from a 1998 study of home-based garment producers. Growing economic success for these garment producers decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 31 publications
4
61
0
Order By: Relevance
“…Moreover, studies that demonstrate a significant or even a limited positive effect of mobiles on microenterprise profitability are relatively scarce (see, for example, Souter, 2005;Kantor, 2005;Jensen, 2007;Esselaar et al, 2008;Aker, 2008). Furthermore, only Kantor and Esselaar et al investigated microenterprises in an urban setting, which is the research site of our investigation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, studies that demonstrate a significant or even a limited positive effect of mobiles on microenterprise profitability are relatively scarce (see, for example, Souter, 2005;Kantor, 2005;Jensen, 2007;Esselaar et al, 2008;Aker, 2008). Furthermore, only Kantor and Esselaar et al investigated microenterprises in an urban setting, which is the research site of our investigation.…”
mentioning
confidence: 98%
“…Recent examples include Aminuzzaman et al, 2003;Kantor, 2005;Prasad and Sreedevi, 2007;Buskens and Webb, 2009). One case study (Guihuan, 2005) does however provide some support to the direct impact argument that women benefit from the ICT usage.…”
mentioning
confidence: 99%
“…Regarding gender inequality, literature on female entrepreneurship suggests that the gap between women and men is harmful for social and economic development (Aidis et al 2007;Baughn et al 2006;Terjesen and Amorós 2010, among others). In this regard, Kantor (2005) highlighted that the participation of women entrepreneurs should also be considered in terms of its importance to the home, since it allows for their own development and knowledge transfer to their offspring. To incentivize this process, participation and status improvement of women in the home, job places and society in general, should be achieved.…”
Section: Policy Discussionmentioning
confidence: 99%
“…To incentivize this process, participation and status improvement of women in the home, job places and society in general, should be achieved. Additionally, Kantor (2005) suggested empowering women in terms of financial resource access, childcare infrastructure and management skills. In this case, policies encouraging female participation in entrepreneurial activity and labor market should take into account characteristics such as marital status, presence of children, age, education level and business type (Lee et al 2011).…”
Section: Policy Discussionmentioning
confidence: 99%
“…Many studies have shown that MSME growth is considerably explained by firm age (Haltiwanger, Jarmin & Miranda, 2013), the sector in which it operates (Soderbom & Teal, 2003), ownership structure such as ethnic origins and gender of owners (Kantor, 2005;Raturi & Swamy, 1999) and location (Gelb et al 2007;Aterido & HallwardDriemeier, 2010). On the back of this literature, it is fair to expect that the effect of an obstacle on growth will likewise vary across the categories of MSME such as age, sector, ownership, and location in South Africa.…”
Section: Application Of Analytical Frameworkmentioning
confidence: 99%